The task is to evaluate $$\sum_{k=0}^{n}\dfrac{1}{k+1}{2k\choose k}{2(n-k)\choose n-k} $$

This is what I've gotten so far.

$$\begin{align*} A(x)&=\sum_{n\geq 0}\left(\sum_{k\geq 0}^{n}\dfrac{1}{k+1}{2k\choose k}{2(n-k)\choose n-k}\right)x^{n}\\ &=\sum_{n\geq 0}C_{n}x^{n}\sum_{n\geq 0}\binom{2n}{n}x^{n}\\ &=\dfrac{1-\sqrt{1-4x}}{2x}\cdot\dfrac{1}{\sqrt{1-4x}}\\ &=\dfrac{1}{2x\sqrt{1-4x}}-\dfrac{1}{2x} \end{align*}$$

So we have $$ A(x)=\dfrac{1}{2}\sum_{n\geq 1}\binom{2n}{n}x^{n-1}$$

So the answer would be $\dfrac{1}{2}\binom{2(n+1)}{n+1}$ but I know that is wrong because I got $\binom{2n-1}{n}$ when using a combinatorial arguement, which was verified.


$\dfrac{1}{2}\binom{2n+2}{n+1}=\binom{2n+1}{n}$ I just counted the lattice paths to $(n+1,n+1)$. Don't know why I didn't think of that earlier.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.